EXPLORING THE INFLUENCE OF DIGITAL FINANCIAL LITERACY, DIGITAL BANKING, AND SELF-CONTROL ON STUDENTS SAVINGS BEHAVIOR - Azizah, Nur; Takidah, Erika; Zulaihati, Sri (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
The rapid development of financial technology requires students to have a good understanding of managing finances digitally, but many still face challenges in terms of effective savings behavior. This ponder points to analyze the impacts of digital financial literacy, digital banking, self-control, and saving behavior among undergraduate students.. A quantitative approach was utilized, utilizing surveys as the essential information collection instrument. The populace comprised 676 undergrad understudies from the 2021 cohort, and the test of 245 understudies was decided utilizing the Isaac and Michael equation with a 5% edge of blunder, chosen through a proportional stratified random sampling technique. The comes about uncover that digital financial literacy, digital banking, and self-control altogether and partially impact students' saving behavior. Practically, this research can be a basis for further research and provide input for related parties in improving students' savings behavior.